2018
DOI: 10.22178/pos.32-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors Affecting Implementation of Public Private Partnership Housing Projects in Bauchi State, Nigeria

Abstract: Public Private Partnership (PPP) Housing scheme in Nigeria is intended to complement government effort toward increasing housing stock and providing affordable housing in the country. However, Bauchi state government adopted the construction of 5,000 phases PPP Housing. But 6 years after the commencement of the scheme, only a few numbers of housing units were completed and commissioned. Therefore, it becomes imperative to carry out research on the impact level of those factors affecting the implementation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Egypt, Tunisia, South Africa (Mohammed et al, 2014), and Nigeria have all benefited from public-private partnerships (Ayodele & Ayosike, 2015 cited in Ojwang, [13]). In comparison to industrialized countries, the majority of African countries that adopt the PPP model for housing provision are still in the early phases of development [14], with an insufficient institutional structure (Kavishe et al, 2018).…”
Section: Public Private Partnershipmentioning
confidence: 99%
“…Egypt, Tunisia, South Africa (Mohammed et al, 2014), and Nigeria have all benefited from public-private partnerships (Ayodele & Ayosike, 2015 cited in Ojwang, [13]). In comparison to industrialized countries, the majority of African countries that adopt the PPP model for housing provision are still in the early phases of development [14], with an insufficient institutional structure (Kavishe et al, 2018).…”
Section: Public Private Partnershipmentioning
confidence: 99%
“…Guarini and Battisti (2017) established a feasibility assessment model for social housing PPP project in Italy [22]. Sani et al (2018) investigated the impact factors affecting the implementation of PPP housing scheme for providing affordable housing in Bauchi State, Nigeria [23]. Bockman (2018) studied the impact of PPP on American public housing via a case study [24].…”
Section: Ppp Ideology For Affordable Housing Financingmentioning
confidence: 99%
“…The model should consider that development of down market urban housing is faced by many risks like political, financial, construction, operation and maintenance, demand, legal and revenue generation, which have a cost element. The financing model for PPPs should have an appropriate mix of equity and debt ratios, adequate costing of the risks, and due considerations for the project"s unique conditions and environment, alongside the need for public sector support (African Affordable Housing Institute, 2018; Sani et al, 2018;Kwak et al, 2009). Research has found out that successful application of PPPs requires favourable existence of political, legal, economic and commercial environments to allow optimum participation of the private sector in developing down market urban housing.…”
Section: Successful Ppps Applicationmentioning
confidence: 99%
“…Thirteenth is the need for adequate government guarantees. This should be done through thorough assessment of the costs and benefits (Affordable Housing Institute, 2018; Sani et al, 2018;Kutana, 2017;Ismail, 2013;Mathonsi, 2013; UN Habitat, 2011;Kwak et al, 2009).…”
Section: Successful Ppps Applicationmentioning
confidence: 99%